Blowing smoke : why the right keeps serving up whack-job fantasies about the plot to euthanize grandma, outlaw Christmas, and turn junior into a raging homosexual /: why the right keeps serving up whack-job fantasies about the plot to euthanize grandma, outlaw Christmas, and turn junior into a raging homosexual. (2010) - Unknown
No abstract available